Environmental management program based on ISO 14001 standards for the sustainability of the universities - Morales Ramos, Jorge Guillermo (2019)
The overall goal of this research is to develop an Environmental Management Program which promotes sustainability in universities located in the region of Lambayeque for further implementation. In this regard, the research carried out raises the question: How does the design of an Environmental Management Program, based on ISO 14001, contribute to the sustainable development of universities located in the region of the Lambayeque? This research is considering the following hypothesis: the implementation of an Environmental Management Program based on ISO 14001 will contribute to sustainable development in the universities in the region of Lambayeque. The kind of research belongs to the prospective one with a qualitative approach to respond to the approach to the problem; it aims to establish a comprehensive perspective on reality and integrate the research in a multidisciplinary way. The preliminary diagnosis and the results obtained states that universities located in Lambayeque do not have an environmental management system and that only one of them applies an Environmental Management Program in an isolated context. The analysis of the Management Program proposed when implemented will benefit the community in general and to the universities in Lambayeque.